If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(-19) = -28 Multiply -1 * -19 x + 19 = -28 Reorder the terms: 19 + x = -28 Solving 19 + x = -28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + x = -28 + -19 Combine like terms: 19 + -19 = 0 0 + x = -28 + -19 x = -28 + -19 Combine like terms: -28 + -19 = -47 x = -47 Simplifying x = -47
| -7(w+6)-(2w-9)=-10w | | 3/5=b/100 | | 4m+7=3m-12 | | 5×k-9=2/3j,j | | 8x^2=16-8x | | 6/2=9/a | | -0.6x=15.96 | | 3x=8+3x-30+3x | | 0.05+200.00=0.10x+75.00 | | 3x-21=9+4x | | -10x+8=-132 | | p=200+5q | | n*4=88 | | 14x+x+15=18x+6 | | p^2+4p-18=0 | | X^2=8x+13 | | Q=200+5P | | -x/6=-18 | | 5x^2-80x+150=0 | | 8b+16=68 | | 46,000=2/3x | | 16=52-m | | X+105+x+72=161 | | 1/3(nx4)=33 | | 5x^3-80x^2+150=0 | | 10(x+7)=10(x+14) | | x/-36 | | 5/18-x-2/9x-4/6 | | 2.3x-6.8=3.1 | | x+0.07x=38.5 | | 5(t-3)-2t=33 | | (1/(x^5))=32 |